Next‐generation sequencing as a tool for breakpoint analysis in rearrangements of the globin gene clusters. (May 2017) - Clark, B. E.; Shooter, C.; Smith, F.; Brawand, D.; Thein, S. L.
Abstract: Introduction: Next‐generation sequencing (NGS), now embedded within genomic laboratories, is well suited to the detection of small sequence changes but is less well adapt for detecting structural variants (SV), mainly due to the relatively short sequence reads. Of the available target enrichment methods, bait capture or whole‐genome sequencing appears better suited to detecting SV as there is less PCR amplification and is therefore more representative of the genome being sequenced. Material and methods: In 2015, we described the first inversion/deletion causing εγδβ‐ thalassemia using an NGS approach, with base‐pair resolution. Bioinformatic processing of the sequencing data was manual and time‐consuming. The methodology relied on detecting the presence or absence of the SV by assessing sequence coverage and then mapping the deletion by capturing and sequencing breakpoint spanning reads (split reads). In the period between developing more automated analytical methods, we identified the first duplication of the entire beta globin cluster. Results: Detecting the presence of the SV is reliable but capturing the breakpoint spanning reads is challenging. Confirmation by Sanger sequencing a breakpoint spanning amplicon has confirmed the NGS results in all cases. Conclusions: We have now streamlined and automated the bioinformatic approach using Exome Depth to assess sequence coverage and Delly to detect split and discordant reads. The combined NGS and bioinformatic strategy has proven to be highly successful and applicable to routine diagnostics.